A novel approach of solid waste management via aromatization using multiphase catalytic pyrolysis of waste polyethylene - Gaurh P.; Pramanik H. (My University, 2025)
A new and innovative approach was adopted to increase the yield of aromatics like, benzene, toluene and xylene (BTX) in the catalytic pyrolysis of waste polyethylene (PE). The BTX content was significantly increased due to effective interaction between catalystZSM-5 and target molecules i.e., lower paraffins within the reactor. The thermal and catalytic pyrolysis both were performed in a specially designed semi-batch reactor at the temperature range of 500 °C–800 °C. Catalytic pyrolysis were performed in three different phases within the reactor batch by batch systematically, keeping the catalyst in A type- vapor phase, B type- liquid phase and C type- vapor and liquid phase (multiphase), respectively. Total aromatics (BTX) of 6.54 wt% was obtained for thermal pyrolysis at a temperature of 700 °C. In contrary, for the catalytic pyrolysis A, B and C types reactor arrangement, the aromatic (BTX) contents were progressively increased, nearly 6 times from 6.54 wt% (thermal pyrolysis) to 35.06 wt% for C-type/multiphase (liquid and vapor phase). The pyrolysis oil were characterized using GC-FID, FT-IR, ASTM distillation and carbon residue test to evaluate its end use and aromatic content. © 2017 Elsevier Ltd